“Profesora is doing a great job!” or “Online learning sucks”: The relationship between students’ profiles and online language learning - Wu, Ching-Hsuan; Robles-Puente, Sergio; Thompson, Amy S. (Studies in Second Language Learning and Teaching, 2024)
The impetus of this study is to investigate students’ attitudes towards online language learning based on their previous academic experiences and year of study, including the decision to major or minor (i.e., motivation). A total of 975 students completed a survey questionnaire consisting of background information, Likert scale items, and open-ended questions. The quantitative data were analyzed using an exploratory factor analysis and one-way ANOVAs and were complemented with qualitative data based on students’ responses. Findings indicate that students generally want consistent access to online learning, and that students with prior online-learning experience or with a desire to take an online course presented a statistically significant more positive perception of online language classes. There were also differences in perception of success in the online classes between those students who intended to major or minor in the language and those who did not. The results further revealed a decline in perception of success in online classes with the higher-level classifications (i.e., year of study). This study provides baseline attitudinal data to be built upon in future research and informs stakeholders of language programs in their curricular decisions.